2012
DOI: 10.1080/09658416.2012.742906
|View full text |Cite
|
Sign up to set email alerts
|

Using a genre-based approach for writing instruction in a less-commonly-taught language

Abstract: Although a great majority of the L2 writing literature focuses on teaching Englishlanguage writing, scholars have begun to explore the teaching of writing in other second and foreign languages (FLs), including French, Spanish, German, Arabic, Japanese, and Chinese. However, to our knowledge, no work exists exploring the exigencies of teaching Turkish or Turkish-language writing in North America. This article focuses on Turkish-language instruction, especially Turkish-language writing instruction, in one US uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
(56 reference statements)
2
3
0
1
Order By: Relevance
“…The most beneficial aspects in this regard were the more structured, genre-compatible and complex writing exercises during the joint construction phase of the lessons, and the feedback given by the instructor during the reflection phase. These results were in line with the data obtained in the study of Argıt and Özer-Griffin (2015), Chen andSu (2012), Kuiper, et al (2017) and the possible outcomes suggested by Yiğitoğlu and Reichelt (2014). The third important development point was the order in the physical structure of the text.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The most beneficial aspects in this regard were the more structured, genre-compatible and complex writing exercises during the joint construction phase of the lessons, and the feedback given by the instructor during the reflection phase. These results were in line with the data obtained in the study of Argıt and Özer-Griffin (2015), Chen andSu (2012), Kuiper, et al (2017) and the possible outcomes suggested by Yiğitoğlu and Reichelt (2014). The third important development point was the order in the physical structure of the text.…”
Section: Discussionsupporting
confidence: 89%
“…In regard to this method's success, many studies show how this method significantly improves foreign language writing skills (Carstens, 2009;Chen & Su, 2012;Correa & Echeverri, 2017;Hyland, 2003;Hyland, 2004;Hyland, 2009;Hyon, 1996;Kuiper et al, 2017;Martin & Rose, 2007;Martin & Rose, 2008;Ramos, 2015;Rose, 2008;Rose, 2012;Troyan, 2016). Also, it has showed the same success in Turkish as a foreign language writing lessons, which is the main field of study of this research (Argıt & Özer-Griffin, 2015;Yiğitoğlu & Reichelt 2014).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Other relevant studies have also been conducted both in ESL and EFL settings, for instance, Ahn (2012); Carstens (2009); Chen and Su (2012); Emilia (2005); Firkins et al (2007); Hyon (2001); Kongpetch (2006); Macken-Horarik (2002); Myskow and Gordon (2009); Paltridge (2004); Pujianto et al (2014); Rothery (1996); Trong (2011); Ueasiriphan and Tangkiengsirisin (2019); Xu (2005) and Yigitoglu and Reichelt (2014). Yet, the existing research was restricted to support the teaching of one language skill only, namely writing.…”
Section: Introductionmentioning
confidence: 99%